CONFLICT IN MARRIAGE AND THE USE OF POSITIVE PSYCHOTHERAPY - Kahveci, Müedin; Çobanoğlu, Gizem (International Scientific Journal Vision, 2024)
Positive Psychotherapy is a comprehensive therapy approach that helps couples understand the conflicts they experience in their relationships, discover their inner talents, and communicate more healthily. This approach evaluates the lives of individuals in four dimensions and applies the therapy process step by step by using unique models such as the "Balance Model" and "Five-Step Therapy". The therapy process consists of a five-stage process that guides couples to understand the conflicts in their relationships, discover themselves and find healthier solutions. This process provides couples with a framework for them to better understand themselves and improve their relationship. Marriage is the process of two people by coming together with mutual love, respect and commitment, living together and growing together in line with common goals. Marriage is a form of union in which emotional bonds are established between couples, trust is provided and responsibilities of living together are shared. While Positive Psychotherapy is influenced by a variety of theories and techniques, it provides a broad perspective to couples by offering a holistic approach and supports them in accordance with their unique needs. The purpose of this approach is to help couples have a happier and more satisfying relationship.